Identification of Potential and Product Development Strategies for Micro, Small and Medium Enterprises (UMK) in Sunan Giri Religious Tourism, Giri Village, Gresik Regency - Ayun Maduwinarti MP; IGN Anom Maruta; Dea Putri Erdianto; Johan Afriel Nasrullah (Institute of Computer Science (IOCS), 2021)
The tomb of Sunan Giri is one of the religious destinations located in Bukit Giri in Giri Gajah Village, Kebomas District, Gresik Regency. Several supporting facilities such as a shopping center for various products are sold at the Tourism Market as a center for selling MSEs. Transportation accommodation to the tourist area is quite complete where there are public transportation, motorcycle taxis, and gigs. However, the MSE products sold are still very limited both in terms of quality and quantity. The products sold are various, ranging from food, drinks, crafts, books related to the Islamic religion, skullcaps and crafts related to religious tourism to Sunan Giri's tomb. The problem is that the potential for MSEs has not been identified and the MSE product development strategy in Sunan Giri's religious tourism has not been implemented optimally. The purpose of the research is to identify the potential and develop a strategy for developing MSE products. Research Outputs: 1.Research Report that can be used as input for relevant agencies and MSEs in Sunan Giri religious tourism. 2. Enrichment Journal: Journal of Management: Sinta 4. The research method used is a qualitative descriptive method, with a sample of several MSEs in Sunan Giri religious tourism. Research Results: Based on the results of the SWOT analysis, the right MSE development strategy in Giri Village, District, was obtained, namely the SO (Growth) Strategy. SO strategy is a strategy that utilizes existing strengths to increase its competitive advantage. Through the SO (Growth) strategy, MSEs in Giri Village, Gresik Regency are expected to carry out product development.